Acceptability of egg powder among nursing mothers in rural areas of Ijebu North local government area of Ogun State, Nigeria (2018)
Eggs are among the most nutritious foods, cheapest source of protein, vitamins and minerals. However, fresh egg is fragile and its quality deteriorates easily. Egg powder adds consistent performance to the list of attributes of the commodity hence the need to evaluate the acceptability of egg powder among nursing mothers as a source of protein. The study was carried out in rural areas of Ijebu North Local Government Area of Ogun State. Random sampling technique was used to select 120 respondents across five maternity health centres. Interview schedule was used to collect data. Data were analysed using both descriptive and inferential statistics at α0.05. Findings revealed that 62.5% of the respondents had low level of awareness about egg powder, more than half (55.8%) had unfavourable disposition towards egg powder, resulting in 60.0% of them having low acceptability for its use. Non-availability of egg powder (50.8%) and lack of information on egg powder (50.0%) were major constraints to egg powder consumption in the study area. Significant relationship existed between respondents’ income (χ2 = 0.184), level of education (χ2 = 0.233), awareness (r = 0.229), perception of egg powder (r = 0.246) and the level of acceptability of egg powder. There was a low level of egg powder acceptability in the study area. Hence, there is a need to create awareness on the nutritive value of egg powder in the study area.